2009
DOI: 10.2208/kaigan.65.501
|View full text |Cite
|
Sign up to set email alerts
|

Model for Predicting Bathymetric and Grain Size Changes Based on Bagnold's Concept and Equilibrium Slope Corresponding to Grain Size Composition

Abstract: A model for predicting bathymetric and grain size changes considering equilibrium slopes corresponding to the composition of grain size and each grain size was incorporated with the BG model proposed by Serizawa et al. (2006). The model was applied to the beach changes on Kemigawa Beach. The cross-shore sorting of sand, in which the grain size gradually decreases with increasing depth, and the formation of a gradually changing longitudinal slope were reproduced well. The model was further applied to predict sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The beach changes were reproduced using the contour-line-change model considering grain size changes proposed by Noshi et al (2009) given the bathymetry and the predicted wave conditions. It was found that the local shoreline rotation was triggered by an anthropogenic factor, i.e., the dredging of the reef flat, and the change in wave direction due to the formation of a deep embayment on the reef flat was the direct cause of the shoreline rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beach changes were reproduced using the contour-line-change model considering grain size changes proposed by Noshi et al (2009) given the bathymetry and the predicted wave conditions. It was found that the local shoreline rotation was triggered by an anthropogenic factor, i.e., the dredging of the reef flat, and the change in wave direction due to the formation of a deep embayment on the reef flat was the direct cause of the shoreline rotation.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the data obtained from monitoring surveys after beach nourishment had been completed were analyzed, and a further beach survey and sampling of the seabed materials were carried out on August 23, 2008. On the basis of these data sets, numerical simulations using the contour-line-change model proposed by Noshi et al (2009), considering the equilibrium beach slope corresponding to each grain size and its composition, were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of fine sand discharged offshore was sufficiently small for its effect to be neglected in this study. Such an effect can be accurately predicted using the BG model considering the grain size of sand proposed by Noshi et al (2009). …”
Section: Effectiveness Of Spur Dike As Measurementioning
confidence: 99%
“…Then, Noshi et al (2009) proposed the cross-shore sand transport equation for the contour-linechange model (Eq. (12)), using this method to calculate the local longitudinal slope corresponding to the composition of each grain size.…”
Section:  mentioning
confidence: 99%
“…In fact, the longitudinal slope gradually becomes gentle with increasing content of fine sand, for example, in the wave-shelter zone, but these changes in the local slope in and around the wave-shelter zone due to this mechanism cannot be predicted by their model. Noshi et al (2009) improved the model using the contour-line-change model and taking the equilibrium slope corresponding to each grain size and its composition into account. Although the applicability of this contour-line-change model to practical problems is high, the handling of complicated boundary conditions around various structures is more difficult compared with the BG model proposed by Serizawa et al (2007), in which the fundamental equations are solved in a mesh.…”
Section: Introductionmentioning
confidence: 99%